Effects of Dance on Pain in Patients with Fibromyalgia: A Systematic Review and Meta-Analysis. (1st October 2018) - Murillo-García, Álvaro; Villafaina, Santos; Adsuar, José C.; Gusi, Narcis; Collado-Mateo, Daniel
Abstract : Objective . The aim of this study was to perform a systematic review on the effectiveness of dance-based programs in patients with fibromyalgia, as well as calculate the overall effect size of the improvements, through a meta-analysis. Methods . The Cochrane Library, Physiotherapy Evidence Database (PEDro), PubMed, TRIP, and Web of Science (WOS) were selected to identify the articles included in this systematic review and meta-analysis. A total of seven articles fulfilled all inclusion and exclusion criteria. PRISMA guidelines were followed in the data extraction process. The level of evidence was established following guidelines from the Dutch Institute for Healthcare Improvement (CBO). Results . The studies were all randomized controlled trials, but not double-blind. Duration of dance programs ranged from 12 to 24 weeks. Sessions lasted between 60 and 120 minutes and were performed 1-2 times per week. The overall effect size for pain was -1.64 with a 95% CI from -2.69 to -0.59 which can be interpreted as large. In addition, significant improvements were observed in quality of life, depression, impact of the disease, anxiety, and physical function. Conclusion . Dance-based intervention programs can be an effective intervention for people suffering from fibromyalgia, leading to a significant reduction of the level of pain with an effect size that can be considered as large. However, findings and conclusions from this meta-analysis must be taken with caution due to the small number of articles and the large heterogeneity.